2019
DOI: 10.1177/1363461519853639
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to care and psychopathology among Bolivian migrants living in São Paulo, Brazil

Abstract: The objective of this study was to investigate barriers to appropriate mental health care in a sample of Bolivian migrants living in São Paulo and to examine the association between barriers of care and the presence of symptoms of non-psychotic psychiatric disorders in this population. Considering that treatment usually reduces symptoms, it could be hypothesized that individuals reporting more barriers to care also will report more symptoms. The sample comprised 104 individuals born in Bolivia, with Bolivian n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…Despite these alarming findings, to date the effect of psychological distress on the use of mental health services and its relationship with the barriers to such use in this population have not been investigated. This is despite the fact that previous studies have shown psychological distress to be significantly associated with mental health service use and with perceived barriers to service use among women and minorities [25][26][27].…”
Section: Arab Women In Israel: Mental Healthmentioning
confidence: 63%
See 2 more Smart Citations
“…Despite these alarming findings, to date the effect of psychological distress on the use of mental health services and its relationship with the barriers to such use in this population have not been investigated. This is despite the fact that previous studies have shown psychological distress to be significantly associated with mental health service use and with perceived barriers to service use among women and minorities [25][26][27].…”
Section: Arab Women In Israel: Mental Healthmentioning
confidence: 63%
“…We also think that the sociocultural changes taking place in Arab society in Israel improve mental health literacy, and attitudes to mental illness, its treatment, and stigma [35], factors that may also explain the low perceived barriers among Arab women in our sample. Finally, the low levels of psychological distress among the participants may also explain this finding: Bustamante et al [26], for example, found that mental health symptoms and perceived need for mental health treatment are positively related with perceived barriers to mental health service utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the process of sociocultural change in Arab society in Israel has been shown to positively affect mental health literacy, prevailing attitudes to mental illness, treatment, and stigma (Al-Krenawi, 2019), and this may therefore have also positively affected the perceptions of barriers to mental health services. Third, it is possible that the sample's clinical characteristics such as psychological symptoms and perceived need, which we did not examine, influenced the findings, especially given the positive association between these characteristics and perceived barriers to mental health service use (Ugarte Bustamante et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Local and regional studies have reported adverse mental health outcomes in immigrants. 3,4 Other studies have described psychiatric treatment experiences with refugees and the development of specialized assistance programs. 5,6 However, there is still a lack of data about mental health issues in this population.…”
mentioning
confidence: 99%